Achirality via graphs - Azram, Mohammad (2010)
This article is devoted to establish relationship between knots and planar graphs. This relationship enables us to investigate the total numbers of regions and their relationship with corresponding crossings in a reduced alternating achiral knot. It has been shown that the numbers of regions in a reduced alternating achiral knot is always even and the number of crossing is always two less than the number of regions. Finally we were able to establish necessary conditions for achirality